A hybrid decoding of Reed–Muller codes. (February 2017) - Li, Shuang; Zhang, Shicheng; Chen, Zhenxing; Kang, Seog Geun
In this article, a hybrid decoding algorithm for Reed–Muller codes is presented. Unlike the conventional algorithm, the presented algorithm ends recursive decomposition whenR ( 1, m ) andR ( m − 1, m ) appeared. A simplified maximum-likelihood algorithm based on fast Hadamard transform is also exploited to decode the systematic code through its special structure. As a result, the presented hybrid decoding algorithm reduces the number of floating-point multiplications significantly as compared with the conventional algorithms. In addition, the new algorithm has better error performance than the conventional ones.